Directed Orientation of Oligo(phenylene ethynylene)s Using Ureas or Urethanes in Rod–Coil Copolymers. Issue 22 (12th October 2017) - Ahner, Johannes; Micheel, Mathias; Enke, Marcel; Zechel, Stefan; Schubert, Ulrich S.; Dietzek, Benjamin; Hager, Martin D.
Abstract: Interchromophoric interactions between oligo(phenylene ethynylene)s incorporated in copolymers in solution as well as in solid state are investigated using UV/Vis and IR spectroscopy. One promising strategy to enable strong interchromophoric interactions is the introduction of hydrogen‐bonding moieties. Together with the tendency of the chromophores to self‐assemble via π–π‐stacking a dense packing of the chromophores within a polymer film can be achieved. In order to demonstrate this strategy, oligo(phenylene ethynylene)s are used as monomers for copolymers using the highly efficient blocked isocyanate route and polymer films are prepared by spin coating technique. The copolymers are prepared by an in situ deprotection of a pyrazol protected bis ‐isocyanate functionalized rigid chromophore followed by subsequent polyaddition using a bis ‐amine or bis ‐alcohol linker unit. The specific introduction of urea as well as urethane moieties enhances coplanarization of the chromophores in the polymer films into well‐organized structures, which can be characterized based on their specific optical properties. Abstract : The specific orientation of π‐conjugated polymers in well‐defined thin films is studied in detail and found to be caused by hydrogen bonding as well as π–π‐stacking. The introduction of urea as well as urethane moieties into π‐conjugated polymers at specific positions results in coplanarization of the rigid chromophores and thus in fine‐tuned optoelectronic properties.